The influence of electronic service quality on customer loyalty with trust as mediating variable on e-banking user - Muhammad Alif Dio Ramadhan; Vidyarini Dwita (Operations Management and Information System Studies, 2021)
This study aims to analyze how the influence of electronic service quality on customer loyalty with trust as a mediating variable on e-banking users of Bank Rakyat Indonesia in Padang City. This study was conducted using quantitative methods. The population of this research is all customers of Bank Rakyat Indonesia in Padang City who use e-banking services. The research sample was 230 respondents. This study uses a structural equation model (SEM) test with smart-PLS 3.0 software. The results of this study include: (1) reliability has no effect on customer loyalty, (2) privacy and security have no effect on customer loyalty, (3) website design has no influence on customer loyalty, (4) customer service and support have a significant influence on customer loyalty, (5) reliability has a significant indirect effect on customer loyalty with trust as a mediating variable, (6) privacy and security have a significant indirect effect on customer loyalty with trust as a mediating variable, (7) website design has a significant indirect effect on customer loyalty with trust as a mediating variable, (8) customer service and support has a significant indirect effect on customer loyalty with trust as a mediating variable.